Health Education and Prospective Brides and Grooms Perceptions of Tetanus Toxoid Immunization: A Scoping Review - Ayu Idaningsih; Nita Arisanti; Endang Sutedja; Hadi Susiarno; Elsa Pudji Setiawati; Meita Dhamayanti (JTP - Jurnal Teknologi Pendidikan, 2026)
Maternal and neonatal tetanus remains a significant public health issue, particularly in areas with limited healthcare access. Tetanus Toxoid (TT) immunization plays a vital role in preventing this condition, but vaccination coverage among prospective brides remains low in many regions. This scoping review aims to map existing evidence on the influence of health education on the perceptions of prospective brides regarding Tetanus Toxoid (TT) immunization. Using the PRISMA-ScR framework, literature searches were conducted in PubMed, ScienceDirect, and Scopus, yielding 896 records, of which 10 studies met the inclusion criteria. Thematic synthesis identified three dominant themes: the role of health education in improving knowledge, the influence of individual and social perceptions on vaccination intentions, and the gap between knowledge acquisition and actual immunization compliance. The findings highlight that educational interventions such as counseling, booklets, and digital materials consistently improve knowledge and attitudes, yet these improvements do not always translate into completion of TT doses. Barriers related to service availability, administrative inconsistencies, and socio-cultural factors continue to hinder uptake. Strengthening communication skills among health workers and improving service integration between health facilities and marriage administration offices are essential to enhance adherence to TT immunization before marriage.